2007
DOI: 10.1186/1472-6920-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing medical students' attitudes towards learning communication skills – which components of attitudes do we measure?

Abstract: BackgroundThe Communication Skills Attitudes Scale (CSAS) created by Rees, Sheard and Davies and published in 2002 has been a widely used instrument for measuring medical students' attitudes towards learning communication skills. Earlier studies have shown that the CSAS mainly tests two dimensions of attitudes towards communication; positive attitudes (PAS) and negative attitudes (NAS). The objectives of our study are to explore the attitudes of Norwegian medical students towards learning communication skills,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 17 publications
3
80
0
5
Order By: Relevance
“…their feelings towards and experience from the way communication skills have been taught in their school. Evidently, this is the case for studies using the CSAS, in which 13 items measure affective attitudes and only five measure cognitive attitudes (Anvik et al 2007). (1) year 1 > years 2, 3, 4, 5 and 6 (p < 0.05); (2) year 2 > Years 3, 4, 5 and 6 (p < 0.005); 3 year 3 > years 4, 5 and 6 (p < 0.05).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…their feelings towards and experience from the way communication skills have been taught in their school. Evidently, this is the case for studies using the CSAS, in which 13 items measure affective attitudes and only five measure cognitive attitudes (Anvik et al 2007). (1) year 1 > years 2, 3, 4, 5 and 6 (p < 0.05); (2) year 2 > Years 3, 4, 5 and 6 (p < 0.005); 3 year 3 > years 4, 5 and 6 (p < 0.05).…”
Section: Discussionmentioning
confidence: 96%
“…The original questionnaire is presented in a paper by Rees from 2002 and the Norwegian version is available from the corresponding author. In a recent article, we reported that the CSAS mainly measures two factors: five of the 26 items assessing cognitive attitudes and 13 items assessing affective attitudes (Anvik et al 2007). …”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…21 Attitudes towards learning communication skills correlate positively with female gender, personal experience within health service prior to medical studies, and parents' work outside the healthcare sector. 7,19,22 Problem-based curricula and curricula that integrate the teaching of professional skills also foster a positive attitude. 11,16 The relationship between attitudes towards communication skills learning, patient orientation, and self-regulation skills has not been studied.…”
Section: Assessing Attitudes Towards Learning Communication Skills Anmentioning
confidence: 99%
“…They discovered two dimensions of attitudes; positive and negative. Between 2002 and2007, studies in the UK [19], Nepal [20] and Norway [21] have explored students' positive and negative attitudes towards communication skills learning. Rees et al [19] and Shankar et al [20] also correlated these positive and negative attitudes with different student characteristics.…”
Section: Introductionmentioning
confidence: 99%